Online Streaming Services Uses During The COVID-19 Pandemic in Indonesia - Wratsari, Emerensia Tangkas Alma Wratsari; Junaedi, MF. Sheellyana; Mahestu Noviandra Krisjanti (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
The COVID-19 pandemic accelerates the adoption of online streaming service around the world, including online streaming services, which is now starting to be used in Indonesia, like Netflix. This study assumes that consumers search for emotional and instrumental satisfaction when they start to watch any video or live streaming on their digital devices. Therefore, this study is based on two theories about technology adoption: the Technology Acceptance Model (TAM) and Uses Gratification Theory (UGT), to explore perceived ease of use and perceived usefulness from users' perceptions. By adding perceived risk perception related to the COVID-19 pandemic. This study aims to explore users' perceptions of online streaming services and describe their motivation to use the services. This study uses Smart PLS-SEM as analyze tool. There are 203 respondents used in this study. The research result shows that perceived ease of use positively and significantly affects perceived usefulness. Perceived usefulness, ritualized use, and instrumental use positively and significantly affect the intention to use Netflix. However, this study can't prove the effect of perceived ease of use and perceived risk perception on intention to use Netflix. Furthermore, perceived usefulness positively and significantly mediates the effect between perceived ease of use to intention to use Netflix.